Early outcomes of 5-0 prolene gonioscopy-assisted transluminal trabeculotomy in juvenile open-angle glaucoma - Devendra Maheshwari; Shivam Gupta; Madhavi R Pillai; Nimrita Nagdev; Mohideen A Kader; Rengappa Ramakrishnan (Indian Journal of Ophthalmology, 2025)
Purpose: To study the early postoperative efficacy and safety of 5-0 prolene gonioscopy-assisted transluminal trabeculotomy (GATT) in juvenile open-angle glaucoma (JOAG). Methods: This was a prospective, interventional study. Patients with JOAG planned for GATT were included. All patients were evaluated on postoperative days 1, 15, and 30 as well as 3 months and 6 months postoperatively. Baseline and follow-up visits were compared to determine the significant difference in intraocular pressure (IOP), number of antiglaucoma medications (AGMs), and best-corrected visual acuity. Other outcome measures included surgical success, complications, and interventions. Results: Thirty eyes (28 patients) were included, of which 11 eyes had mild-to-moderate and 19 eyes had severe JOAG. Mean IOP reduced from preoperative 23.43 ± 9.65 mmHg to 12.7 ± 5.2 mmHg (P < 0.001) at the end of 1 week and 14.52 ± 7.3 mmHg, 13.83 ± 6.29 mmHg, and 14.00 ± 7.23 mmHg at the end of 1, 3, and 6 months, respectively (P < 0.001). The mean number of AGM reduced from 2.93 ± 0.87 to 0.5 at the end of 1 week and 0.69 ± 1.17, 0.83 ± 0.15, 0.80 ± 0.96, and 0.80 ± 0.96 at the end of 1, 3, and 6 months, respectively (P < 0.001). The cumulative probability of overall success at the end of 6 months was 72.7% in the mild to moderate group and 73.7% in the advanced group (using both criteria 1 IOP ≥6 and ≤21 mmHg or a 20% reduction and criteria 2 IOP ≥6 and ≤18 mmHg or a 25% reduction). Hyphema was the most common complication. Macrohyphema (>1 mm) was seen in one patient, out of which two patients required anterior chamber wash. IOP spikes (>30 mmHg) were seen in two patients. Conclusion: GATT is efficacious and safe with good surgical outcomes in JOAG patients.